Hepatoprotective Activity of Herbal Composition SAL, a Standardize Blend Comprised of Schisandra chinensis, Artemisia capillaris, and Aloe barbadensis - Mesfin Yimam; Ping Jiao; Breanna Moore; Mei Hong; Sabrina Cleveland; Min Chu; Qi Jia; Young-Chul Lee; Hyun-Jin Kim; Jeong-Bum Nam; Mi-Ran Kim; Eu-Jin Hyun; et al. (Journal of Nutrition and Metabolism)
Some botanicals have been reported to possess antioxidative activities acting as scavengers of free radicals rendering their usage in herbal medicine. Here we describe the potential use of “SAL,” a standardized blend comprised of three extracts from Schisandra chinensis, Artemisia capillaris, and Aloe barbadensis, in mitigating chemically induced acute liver toxicities. Acetaminophen and carbon tetrachloride induced acute liver toxicity models in mice were utilized. Hepatic functional tests from serum collected at T24 and hepatic glutathione and superoxide dismutases from liver homogenates were evaluated. Histopathology analysis and merit of blending 3 standardized extracts were also confirmed. Statistically significant and dose-correlated inhibitions in serum ALT ranging from 52.5% (p=0.004) to 34.6% (p=0.05) in the APAP and 46.3% (p<0.001) to 29.9% (p=0.02) in the CCl4 models were observed for SAL administered at doses of 400–250 mg/kg. Moreover, SAL resulted in up to 60.6% and 80.2% reductions in serums AST and bile acid, respectively. The composition replenished depleted hepatic glutathione in association with an increase of hepatic superoxide dismutase. Unexpected synergistic protection from liver damage was also observed. Therefore, the composition SAL could be potentially utilized as an effective hepatic-detoxification agent for the protection from liver damage.